Delineate the transformation of characters thoughts in Lady Chatterley’s Lover - SHAHEEN, K.; SHAHEEN, K.; RAVICHAND, M.; CHITRA, V.B. (International Journal of Psychosocial Rehabilitation, 2020)
D.H. Lawrence was one of the influential novelists of his times, he has written a plenty of works among them one of the notable work is Lady Chatterley’s Lover. Thisnovel contains a lot of changes in the thoughts of characters especially related to their sexual life. He has depicted the real situation of people and intense desire for sex especially when one is forlorn in their marital life. Lawrence explores how characters psychologically deviates their mind to gain happiness and enter in a relation that was not approved by the society, they are searching for their happiness in different ways. This paper aims to analysis how characters thoughts are transform according to the situation in their life.